Globalization and Structural Change: A Case from Tokha Village of Kathmandu - Ghimire, Harihar (Cognition, 2019)
Globalization is the intense of worldwide social relationship and is the development of worldwide networks – social and economic systems that are remote from our individual concerns. Globalization and structural change are at core of current intellectual, social and developmental discourses in Nepal. The main objective of this study is to describe the role of globalization in changing scenario of society and creating new type of society in Peri-Urban area of Kathmandu. For the same, this paper highlights empirically the visible changes in various aspects of institutions. The theory of globalization particularly Sceptics - who question the extent to which globalization has occurred - is applied. Both primary and secondary data were used in this study. This paper is basically based on qualitative data. The results show that slowly and gradually social changes are seen by globalization but structural traditional norms and values are not changing in this area as literatures show in different societies. Another conclusion of this research is that the parents are very disappointed with their children’s future due to access and misused of technology. The overall findings show that the effect of globalization is seen very slowly in Peri-Urban Newar community of Tokha Kathmandu.